2022
DOI: 10.1371/journal.pone.0265892
|View full text |Cite
|
Sign up to set email alerts
|

Lessons learned about willingness to adopt various protective measures during the early COVID-19 pandemic in three countries

Abstract: Background Regarding the COVID-19 pandemic, concerted efforts have been invested in research to investigate and communicate the importance of complying with protective behaviors, such as handwashing and mask wearing. Protective measures vary in how effective they are in protecting the individual against infection, how much experience people have with them, whether they provide individual or societal protection, and how they are perceived on these dimensions. Methods This study assessed the willingness to fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…The first and second aims are more broadly relevant across scientific research. The latter point is especially critical given substantial concerns raised about public trust in science directly related to COVID-19 [43][44][45][46][47][48] . The third point is also used as a framing for assessing policy recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…The first and second aims are more broadly relevant across scientific research. The latter point is especially critical given substantial concerns raised about public trust in science directly related to COVID-19 [43][44][45][46][47][48] . The third point is also used as a framing for assessing policy recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…This finding supports those of Lio et al [ 32 ] and Binte et al [ 33 ], who revealed that individuals with a positive COVID-19 history were less likely to adhere to mitigation measures compared with uninfected individuals who have no prior history of infection. This tends to imply that individuals who were infected and then recovered perceived the disease as posing less risk, which subsequently reduced their protective behaviour [ 34 ]. Another explanation is that individuals who were infected may have had lower levels of compliance because of the sense of security that recovery from infection may provide [ 35 ].…”
Section: Discussionmentioning
confidence: 99%